Epigenetic arsenal for stress mitigation in plants - Gaude, Aishwarya Ashok; Siqueira, Roxiette Heromina; Botelho, Savia Bernadette; Jalmi, Siddhi Kashinath (Biochimica et biophysica acta. General subjects, 2024)
Plant's ability to perceive, respond to, and ultimately adapt to various stressors is a testament to their remarkable resilience. In response to stresses, plants activate a complex array of molecular and physiological mechanisms. These include the rapid activation of stress-responsive genes, the manufacturing of protective compounds, modulation of cellular processes and alterations in their growth and development patterns to enhance their chances of survival. Epigenetic mechanisms play a pivotal role in shaping the responses of plants to environmental stressors. This review explores the intricate interplay between epigenetic regulation and plant stress mitigation. We delve into the dynamic landscape of epigenetic modifications, highlighting their influence on gene expression and ultimately stress tolerance. This review assembles current research, shedding light on the promising strategies within plants' epigenetic arsenal to thrive amidst adverse conditions. •Epigenetic modifications are vital in plant stress responses regulating genome-wide transcriptional activities.•Alterations in chromatin structure, nucleosome positioning, and histone variants contribute to plant adaptation to stress.•Plants exhibit transgenerational epigenetic inheritance and stress memory in response to stress.•Genetic approaches like RNAi-based targeting and CRISPR-Cas systems are employed for site-specific epigenetic modifications.•Epi-breeding aims to modify epigenetic factors in plants to improve agronomically important traits.